Foreign experience of state regulation of innovative activities of enterprises - Ivanova, T. (Ways to Improve Construction Efficiency, 2023)
The article analyzes and summarizes foreign experience in state regulation of innovative activities of enterprises, identifies methods, mechanisms and instruments of state influence on the development of innovations in countries with developed economies. Attention is paid to the systematization of world practices of innovation policy of countries, which allow to determine effective instruments of state regulation in the field of innovations and to build Ukraine’s own innovation module taking into account national development features and modern challenges. Attention is paid to the importance of developing a national economic model of intellectual and innovative development in Ukraine, which will contribute to the creation of an effective innovation environment and the development of innovative solutions in priority sectors of the economy in the process of reconstruction. The works of Ukrainian and international scientists are considered, which lay the foundation for state policy of innovative development based on the experience of economically developed countries. In particular, emphasis is placed on the use in international practice of complex application of methods, forms and instruments of state support for innovative activities of enterprises, which are oriented towards intellectual and innovative development. The main advantages of state regulation of innovative activities in economically developed countries are outlined using the example of the USA, Japan, France, Germany. The study of foreign experience allowed to form the main directions of state policy in the field of innovation and the main types of models of state regulation of innovative development. The main directions for the development of a national model of innovation policy, taking into account international experience, have been identified: optimizing the use of intellectual capital, motivating and stimulating invention and increasing the efficiency of innovative activity; forming and developing an innovative structure by creating innovative clusters that will contribute to the generation of new ideas, their rapid implementation and commercialization; supporting technology exchange by activating the processes of transferring innovative developments from scientific institutions to business using modern digital tools and ensuring reliable protection of intellectual property.